ARTIFICIAL INTELLIGENCE AND PRE SERVICE TEACHER: A STUDY TO ASSESS THE AWARENESS AND KNOWLEDGE - Basharat Kiani; Dr Syed Jawad Zareen Shah; Samra Anjum; Rabia Tabbasum; Faisal Ishaq (International Journal of Contemporary Issues in Social Sciences, 2023)
Teachers have historically played a crucial role in driving societal change. However, the current cohort of prospective teachers enrolled in professional degree programs often lacks an understanding of the applications of artificial intelligence (AI) in classrooms and school environments. The study explores the integration of Artificial Intelligence (AI) education in Azad Jammu & Kashmir (AJK) Pakistan. It addresses the AI education in the AJK to empower educators to effectively introduce AI concepts to students. The research objectives focus on assessing the awareness and knowledge of AI in pre-service teachers and its integration in the curriculum. A mixed-methods approach was used, involving questionnaire comprised of 10 items for pre-service teachers from various universities of AJK. The findings revealed that most participants had a reasonable understanding of AI but felt that the current curriculum lacked sufficient AI content.